A Mediated Account of Corona Languaging - Mohammed Nasser Abdulsada (Pioneer: Journal of Language and Literature, 2021)
This research explores how language mediates Corona or Covid-19. To find out this phenomenon, a few Corona-related words, phrases, and structures are put into discussion. The paper, also, draws on the languaging of Corona, as a global disaster, with a highlight of the practices, attitudes, and discourses expressed over this disaster. First, the paper introduces a generic exposition on the various aspects of global disasters in terms of linguistic structures, which are all supported by some previous researches. Then, a broader interpretation of how language mediates Corona is elaborated. Finally, the paper states a few findings, conclusions, and further areas of research. Language plays a significant role in shaping disasters, and in this concern, the paper revealed that Corona pandemic is highly mediated at the lexical, meta-linguistic, and conceptual levels. Additionally, relating Corona to meta-linguistic aspects can underline a media-catastrophe link, one that may be worth a broader and further investigation.